FMA (Noise) 1989 to OSHA (Noise) 2019 – Is it Worth the Wait? - Razali, Ailin (IIUM Medical Journal Malaysia, 2019)
Occupational health practitioners in our country were heartened following the gazettement of the new regulation with regard to occupational noise exposure in alignment with the Occupational Safety and Health Act (OSHA 1994) by the Attorney General’s Chamber in early June this year.